Caliphate from Ibn Taymiya’s Point of View - Dahoud , Hayel (Dirasat: Shari’a and Law Sciences, 2020)
Ibn Taymiyah has a great presence in Islamic scholarly fields, Islamic groups and streams. Ibn Taymiyah lived in conditioned similar to those in which we live these days in terms of division, and foreigner prevalence, and civil war. In his books and papers, Ibn Taymiyah adressed problems of his era, especially the political ones, regime structure, ruler appointment and its conditions, ruling contract, ruler deposition, and other Islamic political issues. This research presents Ibn Taymiya’s views about the issues of Caliphate and Imamate, and whether they are the only form of ruling or not, and whether other forms of rulings are acceptable or not from an Islamic point of view, for examples Sultanate and Monarchy, the research has reached the conclusion that Ibn Taymiyah see Caliphate while other forms are acceptable as exceptions with the condition of righteousness of Monarch and applying justice. . The study adopted the inductive approach in stating Ibn Taymiyah’s position on the issues raised by the study, then the analytical approach to these statements and deducing Ibn Taymiyah’s position and opinion on the issues of the study.